A New Liver Expression Quantitative Trait Locus Map From 1, 183 Individuals Provides Evidence for Novel Expression Quantitative Trait Loci of Drug Response, Metabolic, and Sex‐Biased Phenotypes. Issue 6 (30th January 2020) - Etheridge, Amy S.; Gallins, Paul J.; Jima, Dereje; Broadaway, K. Alaine; Ratain, Mark J.; Schuetz, Erin; Schadt, Eric; Schroder, Adrian; Molony, Cliona; Zhou, Yihui; Mohlke, Karen L.; Wright, Fred A.; et al.
Abstract : Expression quantitative trait locus (eQTL) studies in human liver are crucial for elucidating how genetic variation influences variability in disease risk and therapeutic outcomes and may help guide strategies to obtain maximal efficacy and safety of clinical interventions. Associations between expression microarray and genome‐wide genotype data from four human liver eQTL studies ( n  = 1, 183) were analyzed. More than 2.3 million cis ‐eQTLs for 15, 668 genes were identified. When eQTLs were filtered against a list of 1, 496 drug response genes, 187, 829 cis ‐eQTLs for 1, 191 genes were identified. Additionally, 1, 683 sex‐biased cis ‐eQTLs were identified, as well as 49 and 73 cis ‐eQTLs that colocalized with genome‐wide association study signals for blood metabolite or lipid levels, respectively. Translational relevance of these results is evidenced by linking DPYD eQTLs to differences in safety of chemotherapy, linking the sex‐biased regulation of PCSK9 expression to anti‐lipid therapy, and identifying the G‐protein coupled receptor GPR180 as a novel drug target for hypertriglyceridemia.